Chlamydia and gonorrhoea contamination of clinic surfaces. Issue 6 (25th April 2012) - Lewis, Natasha; Dube, Gail; Carter, Christine; Pitt, Rachel; Alexander, Sarah; Ison, Catherine A; Harding, Jan; Brown, Louise; Fryer, John; Hodson, James; Ross, Jonathan
Abstract : Introduction: Nucleic acid amplification tests, with their ability to detect very small amounts of nucleic acid, have become the principle diagnostic tests for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) in many sexual health clinics. The aim of this study was to investigate the extent of surface contamination with CT and GC within a city centre sexual health clinic and to evaluate the potential for contamination of containers used for the collection of self-taken swabs. Method: Surface contamination with CT and GC was assessed by systematically sampling 154 different sites within one clinic using transcription-mediated amplification (TMA), quantitative PCR and culture. The caps of containers used by patients to collect self-taken samples were also tested for CT and GC using TMA. Results: Of the 154 sites sampled, 20 (13.0%) tested positive on TMA. Of these, five (3.2%) were positive for CT alone, 11 (7.1%) for GC alone and four (2.6%) for both CT and GC. The proportion of GC TMA-positive test results differed by gender, with 11 (18.3%) positive results from the male patient clinic area compared with one (1.6%) from the female area (p=0.002). Positive samples were obtained from a variety of locations in the clinic, but the patient toilets were more likely to be contaminated than examination rooms (p=0.015). Quantitative PCR and culture assays were negative for all samples. 46 caps of the containers used for self-taken swabs were negative for both CT and GC on TMA testing. Conclusions: Surface contamination with chlamydial and gonococcal rRNA can occur within sexual health clinics, but the quantity of nucleic acid detected is low and infection risk to patients and staff is small. There remains a potential risk of contamination of patient samples leading to false-positive results.